TEACHER FACTORS INFLUENCING SENIOR SECONDARY SCHOOL STUDENT ACHIEVEMENT IN CHEMISTRY - Chinda, W.; Pepple, T.F. (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2021)
The study examined the influence of teacher-related factors on senior secondary school students' achievement in senior school Chemistry in Bayelsa State. For the study, five research questions were formulated. The research adopted the survey design. The population of the study consists of all senior secondary schools in Bayelsa State. There are a total of 297 secondary schools in Bayelsa State. Using the simple random sampling technique, 10 senior secondary schools were selected from five (5) Local Government Areas in the state(2 schools from each of the 5 L.G.A), a school was selected if it had a permanent chemistry teacher. A simple random sampling technique was used to collect data from 200 respondents (10 principals, 10 vice principals, 180 students. Two research instruments were used for the study: The Teacher Quality Questionnaire (TQQ) and Chemistry Achievement Test (CAT). The instruments were validated. The reliability of the instrument was established using appropriate tools. The data collected were analysed using mean and standard deviation The findings of this study revealed that; there is a positive relationship between Teachers academic qualification and students achievement in senior school chemistry, a negative relationship exist between teachers professional qualification and students achievement in senior secondary school chemistry, a positive relationship between teacher years of experience and student achievement in senior school chemistry, a positive relationship exists between teachers exposure on the job training and students achievement in senior school chemistry. The result also showed a positive relationship between chemistry and teachers interest in the subject. It is recommended that the government and stakeholders in education should employ teachers with prerequisite qualifications, experience, exposure on the job training, mastery of the subject matter.